Implementasi Baca Al-Qur'an Metode Qiroati dalam Membentuk Generasi Qur'ani Santri TPA At-Taqwa di Desa Banggle - Wathon, A. (STAI Miftahul ULa Nganjuk, 2023)
This study aims to determine the implementation of the Qiroati method of the Quran reading program to develop a generation of Quran students at the At-Taqwa TPA, Bongle Village, Lengkong District. The results of the study indicate that the Quran reading program implemented by the At-Taqwa TPA with the Qiroati approach has succeeded in producing a generation of Quran students. In addition, this method also helps to increase the love of the Quran. and students' skills in understanding and practicing the teachings of the Quran. Based on the research findings, it is recommended to the At-Taqwa TPA management to improve the training and coaching of Qiroati method Quran teachers. Therefore, the Qiroati method of Quran reading program can be more effective in producing a generation of quality Quran students at the At-Taqwa TPA.